2021
DOI: 10.3389/fgene.2020.612475
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Cross-Linking MS of the Complement System MAC Assembled on Live Gram-Positive Bacteria

Abstract: Protein–protein interactions are central in many biological processes, but they are challenging to characterize, especially in complex samples. Protein cross-linking combined with mass spectrometry (MS) and computational modeling is gaining increased recognition as a viable tool in protein interaction studies. Here, we provide insights into the structure of the multicomponent human complement system membrane attack complex (MAC) using in vivo cross-linking MS combined with computational macromolecular modeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Khakzad et al developed an affinity procedure preceded by a chemical cross-linking on human blood plasma using live S. pyogenes to characterize the multicomponent human complement system membrane attack complex (MAC) associated with the bacterial surface and provided detailed information of protein–protein complexes in their native environment ( 103 ). In the same line, the same authors, early this year combined a targeted XL-MS approach with molecular dynamics (MD) simulations to characterize the S. pyogenes M1 protein (virulence factor) and human-IgG interactions ( 102 ).…”
Section: The Dynamic Host-pathogen Interactions During Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Khakzad et al developed an affinity procedure preceded by a chemical cross-linking on human blood plasma using live S. pyogenes to characterize the multicomponent human complement system membrane attack complex (MAC) associated with the bacterial surface and provided detailed information of protein–protein complexes in their native environment ( 103 ). In the same line, the same authors, early this year combined a targeted XL-MS approach with molecular dynamics (MD) simulations to characterize the S. pyogenes M1 protein (virulence factor) and human-IgG interactions ( 102 ).…”
Section: The Dynamic Host-pathogen Interactions During Infectionmentioning
confidence: 99%
“…The authors revealed important peptides, at the binding interface of the bacterial M1 protein in complex with human IgGs, playing a crucial role in the interactions. Certainly, XL-MS is becoming a routine tool for protein structure determination, conformation analysis, and mapping protein interactions in complex mixtures, as well as intact living cells ( 104 , 105 ), unveiling the structural mechanisms of immune response and bacterial evasion by using a combination of mass spectrometry acquisition techniques such as DDA, DIA, and high-resolution MS1 (hrMS1) ( 102 , 103 ).…”
Section: The Dynamic Host-pathogen Interactions During Infectionmentioning
confidence: 99%
“…The MAC complex is an important part of the immune system, capable of forming a pore to disrupt target cell membranes. Ultimately the authors obtained an average of eight cross-links for each protein interaction interface of the MAC complex, which allowed for assembly of a structural model for MAC from a native environment, highlighting conformational differences from the in vitro generated CryoEM models …”
Section: Ms Structural Biology In Cellsmentioning
confidence: 99%
“…253 Employing a unique, targeted approach to XL-MS, in which a series of computationally predicted structural models are used to guide the MS analysis of cross-linked peptides, 254 researchers from the Malmstrom laboratory have studied the interaction of proteins from human plasma with the Gram-positive bacteria Streptococcus pyogenes. 107 Cross-link derived distance constraints were used to construct a model of the interaction between the M1 protein from the surface of S. pyogenes cells with multiple human plasma proteins including albumin, fibrinogen, serpinA1, IgG, haptoglobin, C4BPa, and F13A1. 254 The interactions between M1 and four subclasses of human IgG were analyzed more in depth with integrative modeling and molecular dynamics simulations revealing important peptide sequences at the binding interface that play a crucial role in the interactions.…”
Section: Genetically Encoded Cross-linking In Living Cellsmentioning
confidence: 99%
“…Finally, the peptide-spectrum matches (PSM), the assignment of the peptide sequences to individual MS spectra, are produced using comprehensive compendia of reference protein sequences database [3]. Some of MS's remarkable applications are in the infection medicine proteomics field, where it is employed to characterize the molecular mechanism behind invasive bacterial diseases [4][5][6], modeling host-pathogen interactions [7][8][9][10][11][12][13] and investigate systemic proteome changes [14][15][16][17][18]. The use of the trypsin protease is justified by its efficiency, stability, and specificity to cleave only at the C-terminal of the basic residues, arginine, and lysine [19].…”
Section: Introductionmentioning
confidence: 99%